Accuracy of Assessment of Eligibility for Early Medical Abortion by Community Health Workers in Ethiopia, India and South Africa. - Heidi Bart Johnston; Bela Ganatra; My Huong Nguyen; Ndema Habib; Mesganaw Fantahun Afework; Jane Harries; Kirti Iyengar; Jennifer Moodley; Hailu Yeneneh Lema; Deborah Constant; Swapnaleen Sen (PLoS ONE, 2016)
OBJECTIVE:To assess the accuracy of assessment of eligibility for early medical abortion by community health workers using a simple checklist toolkit. DESIGN:Diagnostic accuracy study. SETTING:Ethiopia, India and South Africa. METHODS:Two hundred seventeen women in Ethiopia, 258 in India and 236 in South Africa were enrolled into the study. A checklist toolkit to determine eligibility for early medical abortion was validated by comparing results of clinician and community health worker assessment of eligibility using the checklist toolkit with the reference standard exam. RESULTS:Accuracy was over 90% and the negative likelihood ratio <0.1 at all three sites when used by clinician assessors. Positive likelihood ratios were 4.3 in Ethiopia, 5.8 in India and 6.3 in South Africa. When used by community health workers the overall accuracy of the toolkit was 92% in Ethiopia, 80% in India and 77% in South Africa negative likelihood ratios were 0.08 in Ethiopia, 0.25 in India and 0.22 in South Africa and positive likelihood ratios were 5.9 in Ethiopia and 2.0 in India and South Africa. CONCLUSION:The checklist toolkit, as used by clinicians, was excellent at ruling out participants who were not eligible, and moderately effective at ruling in participants who were eligible for medical abortion. Results were promising when used by community health workers particularly in Ethiopia where they had more prior experience with use of diagnostic aids and longer professional training. The checklist toolkit assessments resulted in some participants being wrongly assessed as eligible for medical abortion which is an area of concern. Further research is needed to streamline the components of the tool, explore optimal duration and content of training for community health workers, and test feasibility and acceptability.